Against Individualism and Comparing the Philosophies of Rosemont and Sandel. Issue 2 (3rd May 2016) - D'Ambrosio, Paul J.
ABSTRACT: Against Individualism: A Confucian Rethinking of the Foundations of Morality, Politics, Family, and Religion presents Henry Rosemont's reflection on possible Confucian-based avenues for considering solutions to contemporary moral, political, and spiritual problems. Rosemont contends that the ideologies of capitalist economies, which are based largely on competition, and belief in autonomous individuality, including abstract notions of human rights, are fundamentally unable to deal effectively with many of today's most pressing issues. For example, he argues against appealing to universalist principles in an attempt to dissolve ethical and political tensions between cultures and states. In accordance with this orientation, his work is then best judged on the contributions it makes to constructing new perspectives on the problems addressed rather than how accurately he represents any tradition. In fact, Rosemont readily admits that he may be "unfair" to individualism or "creative[ly] misreading" early Confucianism. In this review article, I will argue that some of the differences Rosemont finds between his Confucian critique of individualism and the communitarian critique of individualism are, in fact, not all that dissimilar. For example, while Rosemont sees Alasdair MacIntyre and Michael Sandel as "individualists, " the general orientation of their communitarian response to libertarianism shares much in common with the Confucian "role ethics" perspective on the person and morality or ethics. In this way, I will argue that while Confucian role ethics and communitarian perspectives certainly have their respective emphases, they also have a lot to offer one another.